Strategies for teaching fractions : using error analysis for intervention and assessment - Spangler, David B. (Thousand Oaks, Calif. : Corwin Press, 2011)
'Analyzing student work for error patterns (such as on a diagnostic test) and then providing timely, specific, and meaningful intervention will decrease the probability that the errors will be repeated in the future. Taking into account academic research on how students learn, Spangler provides a practical intervention model and specific hands-on materials for teachers to use when working with the many students who struggle with fractions. The step-by-step intervention strategies illustrated in this book will result in improved student performance and improved student dispositions towards mathematics. It will contain the following elements: reproducibles for fully functional diagnostic tests practice pages for exercises keyed to the diagnostic tests and error patterns, and pages to practice alternative algorithms and estimation teacher resources for hands-on activities, game sheets and pieces, and more'--Provided by publisher.
Machine generated contents note: Preface Acknowledgments About the Author A Look at the Academic Research:Intervention in the Mathematics Classroom Big Ideas in Fractions and Problem Solving Unit 1: Fraction Concepts Unit 2: Addition/Subtraction of Fractions and Mixed Numbers Unit 3: Multiplication/Division of Fractions and Mixed Numbers Resources: Worksheets, Activities, and Instructional Games (Blacklines) Resources for Fraction Concepts Resources for Addition/Subtraction of Fractions and Mixed Numbers Resources for Multiplication/Division of Fractions and Mixed Numbers Answers for Student Materials References Technology Resources Online Index .
Includes bibliographical references.
Keywords: Fractions -- Study and teaching; Error analysis (Mathematics); EDUCATION / Teaching Methods & Materials / Mathematics